Characteristics of Pre-Lens Tear Film Behavior in Eyes Wearing Delefilcon A Silicone Hydrogel Water Gradient Contact Lenses - Norihiko Yokoi; Yuki Furusawa; Hiroaki Kato; Natsuki Kusada; Chie Sotozono; Petar Eftimov; Georgi As. Georgiev (Diagnostics, 2023)
The pre-lens tear film (PLTF) over (i) delefilcon A silicone hydrogel water gradient (WG; 33–80% from core to surface) contact lenses (CLs) (SHWG-CLs) and (ii) subjects’ own non-WG soft CLs (SCLs) (SO-SCLs) was studied in 30 eyes of 30 subjects to assess the hypothesized PLTF stabilization over SHWG-CLs. In both eyes, delefilcon A SHWG-CLs (DAILIES TOTAL1®; Alcon, Fort Worth, TX, USA) or SO-SCLs were worn. After 15 min of wearing each lens, the tear meniscus radius (TMR, mm), lipid-layer interference grade (IG) and spread grade (SG), and non-invasive breakup time (NIBUT, seconds) were evaluated and compared between the SHWG-CLs and the SO-SCLs. The comparison between the SHWG-CL and SO-SCL groups (SHWG-CL and SO-SCL, mean ± SD) revealed that TMRs temporarily decreased and reached a plateau value after 15 min (0.21 ± 0.06; 0.21 ± 0.06) compared to the value prior to CL insertion (0.24 ± 0.08; 0.25 ± 0.08), with no significant difference between the two groups. The NIBUT, IG, and SG values after 15 min of wearing the CLs were (9.7 ± 3.7; 4.7 ± 4.2), (1.0 ± 0.2; 1.8 ± 1.0), and (1.1 ± 0.4; 1.9 ± 1.5), respectively, and all values were significantly better in the SHWG-CL group (p < 0.0001, p = 0.0039, and p < 0.0001, respectively). We found that compared to the SO-SCLs, the maintenance of the PLTF on the SHWG-CLs was supported by the thicker and more stable PLTF.